Pathways in the nineteenth-century British textile industry.
1 online resource (xx, 516 pages)
Keywords: This collection brings together primary sources on the British textile industry across the long nineteenth-century, a subject that is both global and multidisciplinary. This set provides an extensive range of resources on the calico printing industry, textile warehousing and shipping, and textile waste and recycling.